PRARANCANGAN PABRIK MARGARIN DARI RBDPO (Refined, Bleached, Deodorized Palm Oil) KAPASITAS 10.000 TON / TAHUN - , PUTRI UTAMI RAHMANIA, Wiratni, S.T., M.T., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The needs of margarine is growing recently and to meet those needs Indonesia still import it from other countries this far, that is the reason why it would require an effort to make margarine demand can be met by setting up margarine factory. Margarine is an ingredient which can be used as an additive to food and cooking oil substitute. Margarine factory is expected to meet local margarine needs in Indonesia. By fulfilling the needs of margarine in Indonesia, it has an impact on the reduction in country spending, increasing national economy and social welfare as well. This margarine factory design uses RBDPO (Refined, Bleached, Deodorized Palm ) as raw material, which is derived from palm oil processing factory. The production of margarine is held in several stages. Firstly, RBDPO is mixed with Nickel-Kieselguhr catalyst, then it is reacted with hydrogen gas (H2) in a slurry reactor. This reaction occurs at a temperature of 200 0 C and the pressure of 4 atm. RBDPO will be hydrogenated into RBDHPO (Refined, Bleached, Deodorized, Hydrogenated Palm Oil). The next stage is phase separation of solid fraction and liquid fraction of RBDHPO with dry crystallizer. Solid fraction of RBDHPO mixed with bleaching earth in the bleacher tool and proceed to deodorization process in the deodorizer. After deodorized, RBDHPO is mixed with oil phase ingredients, they are vitamin A and beta carotene, besides it is also mixed with water phase ingredients, they are soya lecithin , TBHQ, skim milk, salt and Na-benzoate. Once mixed with those ingredients, the next process is emulsion stage with emulsifying agent in the emulsifier. The final stage is crystallization stage which is done in Votator at 45 0 C to 9,7 0 C at 10 atm pressure. The factory is designed with a capacity of 10.000 tons/year. The margarine resulted from RBDPO is 7,364.2 tons/year and 63.4 tons/year of hydrogen gas. Heat energy needs of the plant is 2,026,003 kcal/tons of product, the water needs of 15,774 kg/tons of product. This factory will be established in Kualatungkal, Tanjungjabuang Barat Dictrict in Province of Jambi. The area needed is 4,0 Ha. It also needs 187 employees to run the factory. Based on calculation of economin evaluation, it is obtained Fixed Capital Investment (FCI) is US $16,633,250.11 and IDR 108.893.160.100,00